Prevalência de HPH e lesões intraepiteliais escamosas em gestantes - Vieira, Elizabeth Dell Orto (2008)
This work studies the prevalence (cross sectional) on infection by HPV in uterine cervical of pregnant women evaluating the subgroups of HPV more prevalents and the association in relation to the development of squamous intraepithelial lesions. The methodology was constituted of questionary applied to 272 pregnant women independent of pregnant age and of being symptomatic or not in the first medical advice of prenatal besides the collect of cervico vaginal material (vaginal walls, ectocervix and endocervix) to the achievement of conventional oncotic cytology by the method of coloration proposed by Papanicolaou and the test of Capture Hybrid II®. Then it was proceeded the identification of squamous intraepithelial lesions and the presence of HPV virus of high, low and medium oncogenic risk. The results of Capture Hybrid II® were correlated with the cytologic discoveries comparing the frequency of anormal results in both methods. It was also proceeded the association with biosocial aspects which could interfere in the possible development of squamous intraepithelial lesions. The analysis of univariable and bivariable correlations were accomplished with calculus of Qui-squared of Pearson and value p<0,05. The logistic regression was used to estimate the importance of associations. The prevalence of infection by HPV and anormal oncotic cytologies was about 32,3% and 14,0% respectively. The sub groups of HPV of high risk were more prevalent (27,6%) than the ones of low and medium risk. (18,4%) and their association showed to be statistically significant (p< 0,05). The association of genital infection by HPV of high risk with squamous epithelial lesions described on conventional oncotic cytology was more prevalent (8,5%) than with HPV of low and medium risk (5,6%) and had statistical importance (p< 0,05)